An Analytical Approach to Oxide Scale Adhesion on Si-Containing Recycled Steel for Process Waste Reduction - Singthanu, Seksan; Nilsonthi, Thanasak (Engineering, Technology & Applied Science Research, 2026)
This study investigates the oxide scale adhesion behavior on Si-containing recycled hot-rolled steel to provide insights for process waste reduction during descaling. Steel samples with varying silicon (Si) content (0.01 to 0.3 wt.%) were re-oxidized in a 17% H2O-N2 atmosphere at 700-900 °C for 1 min. Quantitative and qualitative assessment techniques were integrated. Phase analysis confirmed hematite (Fe2O3) and magnetite (Fe3O4) formation. Microstructural analysis revealed that scale thickness decreased with rising Si content but increased with temperature. Adhesion was evaluated using an innovative macro-tensile test combined with real-time observation (CCD camera). Quantitative fracture mechanics, utilizing the strain initiating the first scale spallation, were used to calculate the mechanical adhesion energy. The results showed that higher Si content significantly enhanced scale adhesion, with mechanical adhesion energy values being in the 20-40 J/m2 range. This strong adherence is attributed to the potential formation of an Si-rich oxide phase at the steel/scale interface. This integrated assessment confirms that while high Si content promotes a thinner scale (reducing material waste), it simultaneously increases scale tenacity, significantly increasing descaling energy (process waste). For producers, the results emphasize the necessity of tightly controlling Si content in recycled steel inputs below a critical threshold (e.g., 0.2 wt.%) to optimize downstream operations and minimize energy waste.